HISTORICAL STUDY OF MALAY AND CHAM: RELATIONS IN SOCIAL, CULTURAL, POLITICAL AND RELIGIOUS CONTEXTS - Pratama, Fikri Surya; Huda, Teguh Nurul; Ardi, Annisa Azkiya; Suryani, Irma (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
Historical contact between the Indochinese and Malay worlds dates back to the early Bronze Age civilisations of the archipelago. It continued throughout the period of intense trade in the archipelago. Diplomatic relations between the Champa and Malay nations are not limited to economics, but have entered a more intense realm, such as politics, Islamic preaching to a small level, namely kinship. This journal article aims to discuss the history of the relationship between Malay Muslims and the Cham community, especially in building and empowering the Cham Muslim community in Vietnam in the past. The research method used is the historical research method, where source collection uses literature study techniques, with data analysis using interactive patterns. The analysis was carried out from the beginning of the research as well as during the process of analysing the research data sources up to the process of drawing conclusions. The results show that the study of the historical relationship between Champa and Malay has provided insights into the intense relationship between these two nations. This can be seen in how Champa and Malay work together to empower the Cham Muslim community in terms of social, economic, religious and political aspects. The relationship between Malay and Champa is not only romanticised in the past, but this relationship continues to be established and sustained on the basis of culture, humanity and religion.